The effect on the sensitivities of PSA and PSA-age volume score of IPSS and nocturia in predicting positive prostate biopsy findings - O. Üçer; T. Müezzinoğlu; İ. Çelen; G. Temeltaş (African Journal of Urology, 2017)
Objective: The PSA-age volume (PSA-AV) score was calculated by multiplying the age and prostate volume and then dividing the total by the prebiopsy PSA level. The aim of this study was to evaluate the effect on the sensitivities of PSA and PSA-AV score of International Prostate Symptom Score (I-PSS) and nocturia in predicting positive prostate biopsy findings. Subjects and methods: A total of 1302 biopsies data were divided into two groups according to presence/absence of nocturia. Of these biopsies, 452 biopsies data with I-PSS were also divided into three groups according to severity of I-PSS. The sensitivities, specificities, positive and negative predictive values of the PSA-AV and PSA in all the groups were calculated separately. Results: Although the sensitivities of PSA and PSA-AV were similar in the patients with nocturia (94.1% and 95.8%, respectively), the sensitivity of PSA-AV (99.2%) was higher than PSA (91.8%) in the patients without nocturia. The sensitivities of PSA in mild, moderate and severe I-PSS group were found to be 100%, 92.9% and 95%, respectively (the sensitivities of PSA-AV were 100%, 94.4% and 88.2%, respectively). While severity of I-PSS was decreasing, although sensitivity of PSA-AV increased regularly, sensitivity of PSA was variable. Conclusions: All our data shows that if we remove most of the factors which effect PSA such as age, prostate volume, prostatitis and BPH, we may increase the sensitivity of PSA for predicting positive prostate biopsy. Further PSA formulas contain of result of some tests (I-PSS, uroflowmetry or postvoiding residue urine) as well as age and prostate volume should increase the sensitivity and specificity of PSA for detecting prostate cancer.